IMPLEMENTASI PROGRAM FORCLIME DALAM MENURUNKAN DEFORESTASI DI KABUPATEN KAPUAS HULU, KALIMANTAN BARAT TAHUN 2019-2021 - Nurhasanah, Anisa Siti; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Forests in Indonesia have the potential for flora, fauna, ecosystems and tropical forests. It turns out that this huge forest potential is still not paid enough attention by Indonesia. At least 286 million hectares of Indonesian forest experienced deforestation from 2001 to 2021. In that period West Kalimantan contributed 40% of deforestation in Indonesia. This deforestation can trigger climate change and threaten the existence of biodiversity and rural communities (indigenous people). Concerns about deforestation require strategic handling. Implementation of the FORCLIME Program is the answer to implementing REDD+ Mitigation in Indonesia. This research discusses the implementation of the FORCLIME program in dealing with deforestation in Kapuas Hulu Regency, West Kalimantan in 2019-2021? This research uses qualitative research methods, with document data collection techniques (document analysis) sourced from books, international and national journals, official government and non-government documents, as well as news and press release activity. The research results show that the implementation of the FORCLIME Program is carried out at three levels. At the national level the strategy focuses on policies, strategies and institutional plans for forest management. At the regional level, providing advice regarding plans, REDD+ readlines, community and community-based forest management through DPMU. At the site/local level, it is an implementation activity Demonstration Area (DA). DA activities include conservation, land use management, increasing knowledge and sustainable community income and demonstration plot agroforestry.